2012
DOI: 10.1104/pp.112.208900
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Origin of N-Linked β-d-N-Acetylglucosamine Monosaccharide Modifications on Arabidopsis Proteins    

Abstract: Many plant proteins are modified with N-linked oligosaccharides at asparagine-X-serine/threonine sites during transit through the endoplasmic reticulum and the Golgi. We have identified a number of Arabidopsis (Arabidopsis thaliana) proteins with modifications consisting of an N-linked N-acetyl-D-glucosamine monosaccharide (N-GlcNAc). Electron transfer dissociation mass spectrometry analysis of peptides bearing this modification mapped the modification to asparagine-X-serine/threonine sites on proteins that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…However, there is experimental evidence showing the intracellular occurrence of N-GlcNAc proteins (i.e., potential cytoplasmic ENGase reaction products) in murine synapses (38)(39)(40). It was also clearly shown that at least some of the N-GlcNAc proteins are formed by the cytoplasmic ENGase activity in plants (20). These results indicate that formation of N-GlcNAc proteins by ENGase may not be a rare event in cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, there is experimental evidence showing the intracellular occurrence of N-GlcNAc proteins (i.e., potential cytoplasmic ENGase reaction products) in murine synapses (38)(39)(40). It was also clearly shown that at least some of the N-GlcNAc proteins are formed by the cytoplasmic ENGase activity in plants (20). These results indicate that formation of N-GlcNAc proteins by ENGase may not be a rare event in cells.…”
Section: Discussionmentioning
confidence: 92%
“…Although the ENGase is believed to be involved in the catabolism of cytosolic free oligosaccharides, recent evidence shows that it can deglycosylate glycoproteins in vivo to generate N-GlcNAc-bearing proteins in Arabidopsis thaliana (20), raising the possibility that this enzyme may also act as a deglycosylation enzyme for misfolded glycoproteins in the cytosol (21,22) (Fig. 1A).…”
mentioning
confidence: 99%
“…A. thaliana proteins bearing this modification were explained as the product of the reaction of the enzyme endo-β-N-acetylglucosaminidase on larger high mannose N-glycans [31]. In animal cells, endoglycosidases are encoded in the genome even if it is not clear if their activity is directed towards glycoproteins, glycopeptides, or free oligosaccharide [32,33].…”
Section: Sugar-peptide Analogs Of Csf114mentioning
confidence: 99%
“…During a study of antibodies expressed in transgenic plants MALDI-TOF analysis allowed the detection of fragments with masses consistent with N-GlcNAc modification [130]. Recently Arabidopsis thaliana proteins that are predicted to transit through the endoplasmic reticulum and Golgi were identified with such N-GlcNAc modifications [131]. During this study a mass labelling method was developed and used to study N-GlcNAc modification of two myrosinases (thioglucoside glucohydrolases, TGG), TGG1 and TGG2, that are also substituted by high-mannose (Man)-type glycans.…”
Section: Plant N-glycan-engasesmentioning
confidence: 99%
“…These data support the hypothesis that ENGases hydrolyze high-Man glycans to produce some of the N-GlcNAc modifications but also suggest that some modifications are generated by another mechanism. It was finally concluded that, since the modification was detected at only one site on each myrosinase, the production of the N-GlcNAc modification may be regulated [131]. This prompts the investigation of the anomeric configuration of the GlcNAc linkage, and also the occurrence of enzymes that transfer GlcNAc to consensus Asn-X-Ser/Thr sites, equivalent to the Haemophilus influenzae glycosyltransferase, able to transfer hexose (Gal or Glc) residues with no requirement for a lipid donor intermediate that has been identified recently [132].…”
Section: Plant N-glycan-engasesmentioning
confidence: 99%